Dimensions of Husband's Social Support and Its Relationship to Postpartum Blues Symptoms in Postpartum Mothers in Mamajang District, Makassar City - Hariani Hariani; Sitti Rahmatiah; Yulianto Machmud; Sukma Saini; Abd Hady Junaidi (Direktorat Politeknik Kesehatan Makassar, 2026)
Postpartum blues remain a common psychological problem among postpartum mothers. Husband’s social support is considered a key factor influencing the occurrence and prevention of postpartum blues. This study examined the relationship between dimensions of husband’s social support and postpartum blues symptoms among postpartum mothers in Mamajang District, Makassar, Indonesia. An analytical quantitative study with a cross-sectional design was conducted among 50 postpartum mothers and 50 husbands selected through purposive sampling based on inclusion and exclusion criteria. Data were collected using a social support questionnaire and the Edinburgh Postnatal Depression Scale (EPDS). Univariate and bivariate analyses were performed using Spearman Rank, Pearson Product Moment, and Chi-Square tests. Postpartum blues symptoms were categorized as mild in 44% of mothers, while 28% were classified as normal and 28% as severe. Husband’s emotional and instrumental support were predominantly high (82–88%), appreciation support was moderate (68%), and informational support was low (54%). All dimensions of social support showed negative associations with postpartum blues symptoms. Emotional, informational, and appreciation support demonstrated weak and non-significant relationships. In contrast, instrumental support showed a significant negative correlation with postpartum blues symptoms (r = -0.319; p = 0.027), indicating its stronger contribution to reducing postpartum blues risk. The findings highlight disparities in both postpartum blues severity and the distribution of social support dimensions. Instrumental support emerged as the most influential protective factor, while other support dimensions contributed positively but less significantly. Active husband involvement through comprehensive social support, particularly instrumental support that addresses physical, psychological, and socioeconomic needs, may effectively reduce postpartum blues symptoms among postpartum mothers.